2017
DOI: 10.1002/1873-3468.12645
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of lysyl oxidase‐mediated extracellular matrix remodeling during mouse decidualization

Abstract: The establishment of decidualization is a prerequisite of successful pregnancy. Lysyl oxidase (Lox) is a copper-containing amine oxidase which catalyzes cross-linking of collagen and elastin in the ECM. Lox is expressed in the subluminal stroma surrounding the implanting blastocyst on day 5 of pregnancy. From days 6 to 8, the signals for Lox mRNA and protein are strongly detected in the decidual cells. The expression of Lox is under the control of estrogen via the GSK-3β/β-catenin/c-myc pathway. Dtprp is decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…These findings indicate that direct contact between the embryo and uterine stroma is required for activation of the PI3K-AKT-FOXO1 pathway as an embryonic survival signal to avoid programmed embryonic death. VEGF, adrenomedullin (ADM), and LOX, which can activate the PI3K-AKT pathway and are regulated by HIF (48)(49)(50), are expressed in the uterine stroma and involved in the process of embryo implantation (15,(51)(52)(53)(54). We found that mRNA expression of VEGF and ADM as well as LOX at the stroma of implantation sites collected by LCM technique was significantly decreased in Hif2a-uKO mice ( implantation.…”
Section: Mice With Uterine Deletion Of Hif2a Show Infertility and Thomentioning
confidence: 93%
“…These findings indicate that direct contact between the embryo and uterine stroma is required for activation of the PI3K-AKT-FOXO1 pathway as an embryonic survival signal to avoid programmed embryonic death. VEGF, adrenomedullin (ADM), and LOX, which can activate the PI3K-AKT pathway and are regulated by HIF (48)(49)(50), are expressed in the uterine stroma and involved in the process of embryo implantation (15,(51)(52)(53)(54). We found that mRNA expression of VEGF and ADM as well as LOX at the stroma of implantation sites collected by LCM technique was significantly decreased in Hif2a-uKO mice ( implantation.…”
Section: Mice With Uterine Deletion Of Hif2a Show Infertility and Thomentioning
confidence: 93%
“…GSK has been shown to modulate many transcription factors, such as AP-1, CREB, and b-catenin (29)(30)(31)(32)(33)(34). AP-1 acts as a transcription factor that regulates cell proliferation, survival, and apoptosis (35).…”
Section: Discussionmentioning
confidence: 99%
“…Lox, also known as protein-lysine 6-oxidase, is rarely detected in normal or non-proliferative senescent HSCs, but is expressed in culture-activated HSCs and intra-hepatic HSCs following CCl 4 injury [30, 31]. Recent studies attributed ECM remodeling, spontaneous reversion of fibrogenesis, and induced phenotypic reversion of HSCs to Lox overexpression [7, 32]. These findings suggested that the dysregulated lncRNA-mRNA network might be closely associated with ECM remodeling and HSC activation.…”
Section: Discussionmentioning
confidence: 99%